Can we look beyond gender social roles in Indian management? - Rai, Soumi (Teorija in praksa, 2018)
The article seeks to explore gender role, bias and social identities that define workplace structures and traditionally masculinised job positions in India. It deals with the problem of creating an unseen psychological bias in both male managers, leading to perceptual stereotypes, and among women themselves, creating an inability to see themselves as being capable of shouldering personal and professional domains with élan rather than guilt. Based on a literature review and analysis of gathered empirical data, we show how it is difficult to expect any rapid change in the perception of gender - from a "women-related issue" to a multipronged perspective - to help penetrate the socially created and self-created glass barriers facing women executives in India.
Keywords: Gender inequality; Management; Managerji; Managers; Spolna neenakost; Stereotipi; Stereotypes; Upravljanje; Women; Ženske